2008
DOI: 10.1073/pnas.0711942105
|View full text |Cite
|
Sign up to set email alerts
|

Delayed antiviral plus immunomodulator treatment still reduces mortality in mice infected by high inoculum of influenza A/H5N1 virus

Abstract: The mortality of human infection by influenza A/H5N1 virus can exceed 80%. The high mortality and its poor response to the neuraminidase inhibitor oseltamivir have been attributed to uncontrolled virus-induced cytokine storm. We challenged BALB/c mice with 1,000 LD 50 of influenza A/Vietnam/1194/04. Survival, body weight, histopathology, inflammatory markers, viral loads, T lymphocyte counts, and neutralizing antibody response were documented in infected mice treated individually or in combination with zanamvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
253
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 276 publications
(263 citation statements)
references
References 27 publications
10
253
0
Order By: Relevance
“…All virus strains used in this study were isolated from patients ( Table 1). The virus strains H1/415, H7/ AH1 and H7/ZJ1 were used in our previous studies (Chan et al, 2013b;Chen et al, 2013;Li et al, 2009;Zheng et al, 2008). These viruses were propagated in MDCK cells before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All virus strains used in this study were isolated from patients ( Table 1). The virus strains H1/415, H7/ AH1 and H7/ZJ1 were used in our previous studies (Chan et al, 2013b;Chen et al, 2013;Li et al, 2009;Zheng et al, 2008). These viruses were propagated in MDCK cells before use.…”
Section: Methodsmentioning
confidence: 99%
“…Nitazoxanide, an approved antiparasitic agent with broad-spectrum antiviral activity, could reduce the duration of symptoms in patients with uncomplicated influenza virus infection, but the efficacy in patients with severe illnesses has not been reported (Haffizulla et al, 2014). The combination of celecoxib with neuraminidase inhibitors has shown to exert a synergistic effect in a mouse model (Zheng et al, 2008); and naproxen decreases pulmonary titers in infected mice (Lejal et al, 2013), but no human studies have been reported for these clinically approved non-steroidal anti-inflammatory agents.…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled virus replication can lead to high titers, and even a modest viral load cannot be maintained for more than a few days before death will occur (61). It is of interest to understand how the kinetics of viral load change with increasing infection rate ␤ ␣ .…”
Section: Vol 84 2010 Quantifying Immune Response To Influenza Infecmentioning
confidence: 99%
“…1, 5 Following H5N1 virus infection, systemic and exaggerated release of pro-inflammatory cytokines by rapidly proliferating immune cells and airway epithelial cells results in a cytokine storm and pulmonary damage. A virus-induced cytokine storm has been shown to be highly lethal among young healthy adults, probably due to the strong immune response in these subjects.…”
Section: Introductionmentioning
confidence: 99%
“…6 Although extensive investigations have centered around studying viral genetics, ecology and geography of viral transmission, and clinical diagnosis and management of H5N1 infection, the dysregulated host immune response is much less defined. 5 Interleukin-17 (IL-17), produced by cells of both the adaptive and innate immune systems, functions as a potent pro-inflammatory cytokine and plays a crucial role in both chronic autoimmune pathogenesis 7 and host defenses against diverse pulmonary pathogens. 8 Previous studies have demonstrated that IL-17 plays a beneficial role in infections by various pathogens, including pulmonary Mycobacterium bovis, Klebsiella pneumonia and vaccinia virus.…”
Section: Introductionmentioning
confidence: 99%